Potentially suitable habitat prediction of Pinus massoniana Lamb. in China under climate change using Maxent model - Chi, Yi; Wang, G. Geoff; Zhu, Mengxun; Jin, Peng; Hu, Yue; Shu, Pengzhou; Wang, Zhongxu; Fan, Aifei; Qian, Penghong; Han, Yini; Jin, Songheng (Frontiers in Forests and Global Change, 2023)
Pinus massoniana Lamb. is an important timber species with high ecological and economic value in southern China and a pioneer species for the reforestation of barren mountains. Climate change has had a significant impact on the distribution of many species. To understand the potential geographic distribution of P. massoniana and its response to climate change, this study simulated the potentially suitable habitat and corresponding changes in the distribution pattern of P. massoniana under current and future climate scenarios (SSP1-2.6, SSP2-4.5 and SSP5-8.5) with two periods (2050s and 2090s) based on the Maxent model. Under current climate conditions, the total suitable habitat area of P. massoniana was 2.08 × 106 km2, including 0.76 × 106 km2 of highly suitable habitat, concentrated mainly in Jiangxi and Zhejiang, central and southeastern Hunan, northern Fujian, central and western Chongqing, southern Anhui, central and surrounding areas of Guangdong, central and eastern Guangxi, and northern Taiwan. The areas of moderately suitable habitat and poorly suitable habitat were 0.87 × 106 km2 and 0.45 × 106 km2, respectively. Temperature and precipitation appear to be the most important predictors: precipitation of the driest month (14.7–215.6 mm), minimum temperature of the coldest month (-3.5–13.8°C), annual temperature range (8.1–32.9°C), and mean temperature of the warmest quarter (23.6–34.7°C). P. massoniana are predicted to expand their potential distribution under future climate change: by the end of this century, their total suitable habitat area increased 0.25 × 106 km2 (10.24%) and 0.44 × 106 km2 (16.72%) under the most moderate (SSP1-2.6) and severe (SSP5-8.5) warming scenarios, respectively, by mainly extending northward. Overall, future climate change provided more possibilities for P. massoniana planting and propagation to northern areas, which might be a critical empirical reference for future P. massoniana management practices.